Theoretical and methodological approach to the study of the process of change in the European Accommodation Industry - Rohoza, Mykola; Stolyarchuk, Valentyna (Contemporary trends in business security: Problems and challenges of eastern economies, 2022)
This paper provides insight into current trends of the European Accommodation Industry development through gaining an understanding of processes in the previous period. Based on the result of data analysis of Eurostat online database, it is found out that the accommodation demand in the European Union was unstable during the last decade. The study result shows a trend of the European Accommodation Industry to decrease in the percentage change of nights spent at accommodation establishments by international visitors which has arisen before the impact of COVID-19. Domestic tourism has grown more steadily in the past few years, but it compensates for the current decrease in the international demand only partially. This study confirms that the change in the capacity of the European Accommodation Industry reflects the change in the accommodation demand. This paper results can be used to understand an establishment’s position, identify the threats and opportunities in time of crisis, and to focus its resources on developing unique capabilities that could lead not only to restart activity but to competitive advantage and profitability. To facilitate its realisation by managers, the Process Landscape Model of the core processes and sub-processes of the European Accommodation Industry development has been elaborated.